2010
DOI: 10.1016/j.febslet.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel splice variant of mouse insulin2 mRNA: Implications for insulin expression

Abstract: a b s t r a c tInsulin is a secreted peptide that controls glucose homeostasis in mammals, and insulin biosynthesis is regulated by glucose at many levels. Rodent insulin is encoded by two non-allelic genes. We have identified a novel splice variant of the insulin2 gene in mice that constitutes about 75% of total insulin2 mRNA. The alternate splicing does not alter the ORF but reduces the 5 0 UTR by 12 bases. A reporter gene containing the novel short 5 0 UTR, is more efficiently expressed in cells, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The short 5′UTR splice variant constitutes 75% of the insulin2 mRNA pool, and has an increased translation efficiency [7]. In the present study, we show that miR-196b can specifically target the 5′UTR of insulin2 mRNA (the longer 5′UTR containing a splice variant) and regulates its translation in an Ago2-dependent manner.…”
Section: Introductionsupporting
confidence: 50%
See 4 more Smart Citations
“…The short 5′UTR splice variant constitutes 75% of the insulin2 mRNA pool, and has an increased translation efficiency [7]. In the present study, we show that miR-196b can specifically target the 5′UTR of insulin2 mRNA (the longer 5′UTR containing a splice variant) and regulates its translation in an Ago2-dependent manner.…”
Section: Introductionsupporting
confidence: 50%
“…We have previously shown that specific factors bind to the insulin 5′UTR with differential efficiency [7]. A specific RNA-protein complex is formed with insulin2 5′UTR and cytoplasmic protein factors, but in case of insulin2-S, the complex formation is reduced.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations